2021
DOI: 10.7189/jogh.11.04072
|View full text |Cite
|
Sign up to set email alerts
|

The utility of physiotherapy assessments delivered by telehealth: A systematic review

Abstract: Background Telehealth use is increasing due to its ability to overcome service access barriers and provide continued care when disease transmission is of concern. However, little is known of the validity, reliability and utility of performing physiotherapy assessments using synchronous forms of telehealth across all physiotherapy practice areas. The aim of this systematic review was to determine the current clinometric value of performing physiotherapy assessments using synchronous forms of telehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 78 publications
(241 reference statements)
2
16
0
1
Order By: Relevance
“…Importante mencionar que outras ferramentas tecnológicas têm sido implementadas, como aplicativos e chatbots, buscando otimizar atendimento e reorganizar a oferta de serviços de fisioterapia (ANGARITA; DIANA; GIAIMO, 2017). Embora outros campos da saúde e outras aeaeaeaeaeaea áreas de conhecimento busquem e já estabeleçam aplicativos de smartphones e chatbots para atendimento de suas demandas, no campo da Fisioterapia, ainda é prevalente o teleatendimento, principalmente na modalidade de telerreabilitação (AGOSTINI et al, 2015;SERON et al, 2021;ZISCHKE et al, 2021) Importante mencionar o trabalho de (KOH et al, 2021), que delineia o uso da telerobótica no campo da Fisioterapia, antes mesmo de aperfeiçoamentos e popularização dos chatbots no atendimento e consultoria do fisioterapeuta.…”
Section: Discussionunclassified
“…Importante mencionar que outras ferramentas tecnológicas têm sido implementadas, como aplicativos e chatbots, buscando otimizar atendimento e reorganizar a oferta de serviços de fisioterapia (ANGARITA; DIANA; GIAIMO, 2017). Embora outros campos da saúde e outras aeaeaeaeaeaea áreas de conhecimento busquem e já estabeleçam aplicativos de smartphones e chatbots para atendimento de suas demandas, no campo da Fisioterapia, ainda é prevalente o teleatendimento, principalmente na modalidade de telerreabilitação (AGOSTINI et al, 2015;SERON et al, 2021;ZISCHKE et al, 2021) Importante mencionar o trabalho de (KOH et al, 2021), que delineia o uso da telerobótica no campo da Fisioterapia, antes mesmo de aperfeiçoamentos e popularização dos chatbots no atendimento e consultoria do fisioterapeuta.…”
Section: Discussionunclassified
“…Other studies have shown that there is good agreement between telerehabilitation and face-to-face care for assessment of patients including lower back pain and hamstring flexibility (Palacín-Marín et al (2013);Moral-Muñoz et al (2015)) Additionally, telerehabilitation was shown to be effective following primary total hip or knee arthroplasty that did not compromise quality compared to face-to-face care and had high patient satisfaction (Kuether et al (2019)). When contemplating telerehabilitation physical therapists (PT) should consider patient preference, assessment requirements, culutural needs, environment, cost, access, and confidence using technology (Zischke et al (2021)). These studies show the results for online physical therapy have been effective with long term benefits to both the patient and the therapist.…”
Section: Telehealth and Physical Rehabilitationmentioning
confidence: 99%
“…Telehealth has played an increasingly important role in the paediatric setting, with its applications extending beyond speech‐language pathology to physical therapy and psychology services (Havenga et al, 2015 ). Two studies conducted throughout the early stages of the pandemic that explored the role that telehealth services had in facilitating physiotherapy assessments and the provision of psychological services for children indicated that telehealth services played a vital role in facilitating access during the pandemic, especially when in‐person services were unavailable (Payne et al, 2020 ; Zischke et al, 2021 ). However, both studies referenced above left the impression that whilst telehealth services certainly provided access for children and their families, it was dangerous to assume that telehealth services were likely to overtake or replace in‐person services in the future.…”
Section: Introductionmentioning
confidence: 99%